Prevalence and Classification of Maxillary Canine Impaction among Iraqi patients at An-Najaf City - Sarmad M. Hamozi 1, Kareem M. Alghanim1, Yahya Abdali2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Canines play an important role in functional occlusion, occlusion protection and in aesthetic smile. So the proper knowledge of permanent canine impaction incidence and its position is essential before orthosurgical procedures. The aim of this study is to highlight the prevalence and difficulty of the treatment of maxillary impacted canine. A 1995 panoramic radiographs were taken, total number of males were 737 (37%) and 1258 (63%) were females, a 79 (3.9%) patients were diagnosed with canine impaction where females were 3.6 times more than males, also most patients diagnosed with unilateral, right-sided and type II impactions.